Tanggung Gugat Perebedaan Luas Tanah Secara Faktual dengan Luas Tanah di Sertifikat - Ida Ayu Febri Anasia Dewi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
The purpose of this paper is to find out how to liability for differences in the land area in fact with the land area in the certificate. At the end of this paper, two things are concluded. First, the measuring letter has a function when a technical error/change about the physical data of a plot of land which results in changes in the size and extent of the land, in addition to also explaining the location, extent and boundary of a plot of land or from a flat unit. Second, in order to make a measurement letter, the measurement of the area of the land is carried out and it turns out there is negligence, then what can be obtained by the aggrieved party is a form of preventive legal protection, namely the legal subject has the right or opportunity to submit opinions or objections in order to anticipate the emergence of disputes while the consequences of such negligence can be brought against the related officials in the form of personal liability.